APLIKASI METODE TAGUCHI DALAM PENGENDALIAN KUALITAS PRODUKSI - Ermawati Ermawati; Hartati Hartati (Teknosains, 2014)
The grocery industry at present experiencing a pretty tight competition, so it requires that producers are able to maintain and improve the quality of products produced in order to compete with its competitors in the market. One way to improve the quality of the resulting bread is to regulate the composition of the raw material for making the bread by means of a method of designing an experiment by taking into account the factors that influence or commonly called the Taguchi method.This research aims to find a combination of raw materials each level factors that produce the optimum quality characteristics by using the Taguchi method. The results of this research showed that the combination of factor levels wich produce the optimum quality characteristics of bread are a factor A (flour) at a level of 200 grams, the factor C (butter) at level 2 as much as 10 grams, and factor D (egg) at level 1 as 90 grams. Percent greatest contribution to the quality of bread as compared with other factors, namely 33.12%, 30.62% and 30.61%.